Pancreatic Secretory Trypsin Inhibitor (SPINK1) Gene Mutation in Patients With Acute Alcohol Pancreatitis (AAP) Compared to Healthy Controls and Heavy Alcohol Users Without Pancreatitis - Nikkola Anssi; Mäkelä Kari Antero; Herzig Karl-Heinz; Mutt Shivaprakash Jagalur; Prasannan Aishwarya; Seppänen Hanna; Lehtimäki Terho; Kähönen Mika; Raitakari Olli; Seppälä Ilkka; Pakkanen Pihla; Nordback Isto; et al. (MDPI, 2025)
Only 3–5% of heavy alcohol users develop acute alcohol pancreatitis (AAP). This suggests that additional triggers are required to initiate the inflammatory process. Genetic susceptibility contributes to the development of AAP, and SPINK1 mutation is a documented risk factor. We investigated the prevalence of the SPINK1(N34S) mutation in patients with AAP compared to heavy alcohol users who had never suffered an episode of pancreatitis. Blood samples for the mutational analysis from patients with first episode (n = 60) and recurrent AAP (n = 43) and from heavy alcohol users without a history of AAP (n = 98) as well as from a control population (n = 1914) were obtained. SPINK1 mutation was found in 8.7% of the patients with AAP. The prevalence was significantly lower in healthy controls (3.4%, OR 2.72; 1.32–5.64) and very low in alcoholics without pancreatitis (1.0%, OR 9.29; 1.15–74.74). In a comparison adjusted for potential cofounders between AAP patients and alcoholics, SPINK1 was found to be an independent marker for AAP. The prevalence of the SPINK1 mutation is overrepresented in AAP patients and very low in alcoholics without pancreatitis. This finding may play a role in understanding the variable susceptibility to AAP found in heavy alcohol users.